Audiological approaches to address the psychosocial needs of adults with hearing loss: perceived benefit and likelihood of use. (22nd July 2021) - Bennett, Rebecca J.; Barr, Caitlin; Cortis, Alex; Eikelboom, Robert H.; Ferguson, Melanie; Gerace, Daniel; Heffernan, Eithne; Hickson, Louise; van Leeuwen, Lisette; Montano, Joseph; Preminger, Jill E.; Pronk, Marieke; et al.
Abstract: Objective: To explore the perceived benefit and likely implementation of approaches used by audiologists to address their adult clients' psychosocial needs related to hearing loss. Design: Adults with hearing loss and audiologists completed separate, but related, surveys to rate their perceived benefit and also their likely use of 66 clinical approaches (divided over seven themes) that aim to address psychosocial needs related to hearing loss. Study sample: A sample of 52 Australian adults with hearing loss, and an international sample of 19 audiologists. Results: Overall, participants rated all of the approaches highly on both benefit and likelihood of use ; the highest ranked theme was Providing Emotional Support. Cohort comparisons showed that audiologists ranked the approaches significantly higher than did adults with hearing loss. Overall, participants ranked the themes higher on benefit than on the likelihood to use scales. Conclusions: Adults with hearing loss and audiologists recognise the importance of approaches that address the psychosocial impacts of hearing loss in audiological rehabilitation. However, both groups placed slightly greater value on the internal-based approaches (the clients own emotional response, empowerment, and responsibility), and slightly less emphasis on the external-based approaches (being supported by communication partners, support groups or other health professionals).